The Acid-Catalyzed 2-O-Alkylation of Substituted 2-Hydroxy-1,4-naphthoquinones by Alcohols: Versatile Preparative Synthesis of Spinochrome D and Its 6-Alkoxy Derivatives - Sabutskii, Yuri E.; Denisenko, Vladimir A.; Polonik, Sergey G. (Synthesis, 2018)
A series of substituted 2-alkoxy-1,4-naphthoquinone derivatives were obtained by acid-catalyzed condensation of substituted 2-hydroxy-1,4-naphthoquinones with propan-1-ol, butan-1-ol, or pentan-1-ol in good yields. Based on this reaction a versatile preparative synthesis of spinochrome D was developed.
Keywords: 2-hydroxy-1,4-naphthoquinones; acid catalysis; 2-O-alkylation; n-alkanol; spinochrome D